Pre‐diagnostic anthropometry and survival after colorectal cancer diagnosis in Western European populations. Issue 8 (7th April 2014) - Fedirko, Veronika; Romieu, Isabelle; Aleksandrova, Krasimira; Pischon, Tobias; Trichopoulos, Dimitrios; Peeters, Petra H.; Romaguera‐Bosch, Dora; Bueno‐de‐Mesquita, H. B(as); Dahm, Christina C.; Overvad, Kim; Chirlaque, Maria‐Dolores; Johansen, Christoffer; et al.
<x xml:space="preserve">Abstract</x> General and abdominal adiposity are associated with a high risk of developing colorectal cancer (CRC), but the role of these exposures on cancer survival has been less studied. The association between pre‐diagnostic anthropometric characteristics and CRC‐specific and all‐cause death was examined among 3, 924 men and women diagnosed with CRC between 1992 and 2009 in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Multivariable Cox proportional hazards models were used to calculate hazard ratios (HRs) and corresponding 95% confidence intervals (CIs). Over a mean follow‐up period of 49 months, 1, 309 deaths occurred of which 1, 043 (79.7%) were due to CRC. In multivariable analysis, pre‐diagnostic BMI ≥30 kg/m2 was associated with a high risk for CRC‐specific (HR = 1.26, 95% CI = 1.04–1.52) and all‐cause (HR = 1.32, 95% CI = 1.12–1.56) death relative to BMI <25 kg/m2. Every 5 kg/m2 increase in BMI was associated with a high risk for CRC‐specific (HR = 1.10, 95% CI = 1.02–1.19) and all‐cause death (HR = 1.12, 95% CI = 1.05–1.20); and every 10 cm increase in waist circumference was associated with a high risk for CRC‐specific (HR = 1.09, 95% CI = 1.02–1.16) and all‐cause death (HR = 1.11, 95% CI = 1.05–1.18). Similar associations were observed for waist‐to‐hip and waist‐to‐height ratios. Height was not associated with CRC‐specific or all‐cause death. Associations tended to be stronger among men than in women. Possible interactions by age at diagnosis, cancer stage, tumour location, and hormone replacement therapy use among postmenopausal women were noted. Pre‐diagnostic general and abdominal adiposity are associated with lower survival after CRC diagnosis.